Exploring the Activities of Religious Ministers and Festival Tourism at the Christmas Celebration in St. Lalibela, Ethiopia: A photo-based essay - Dagnachew Nega; Alexander Trupp; Yen Pek Teh (International Journal of Religious Tourism and Pilgrimage)
Religious festivals represent potential for religious tourism, offering unique cultural and spiritual experiences at destinations. Among the methods for promoting religious festivals as a driver for religious tourism is the use of Photo-based essay tools. While this method is not widely explored in academic research, it holds great promise for tourism and events studies. Photographs have a great value in catching the minds of tourists and creating motivation to travel. This photo essay focuses on the religious ministers at the Christmas celebration in Lalibela, a UNESCO World Heritage site in Ethiopia. Six photo categories were identified. Each category has its own message about the religious festival ceremony. In Lalibela, more than nine hundred religious ministers are found, their vibrant and unforgettable Christmas celebrations at Lalibela’s rock-hewn churches exemplify the enduring allure of religious festivals and underscore the potential for further research to drive development in religious festival tourism at sacred sites.